(untitled) (The International Journal for Scientific Research, 2026)
The legal sector is undergoing a rapid transformation driven by automation and digital technologies. Some traditional legal tasks, such as contract drafting, document sorting, legal research, case management, and legal data analysis, can now be performed using smart systems and specialized software. The impact of automation is no longer limited to expediting procedures; it has extended to reshaping the role of the lawyer, the nature of the relationship between the lawyer and the client, and the limits of professional responsibility when using technological tools. This research discusses the impact of automation on lawyers in the digital environment. It examines the concept of legal automation, its practical applications, advantages, and professional and ethical challenges, focusing on the Saudi legal environment, particularly regarding client data confidentiality, personal data protection, and restricting the provision of legal services to licensed professionals. The research concludes that automation does not eliminate the role of the lawyer, but rather redefines it. The modern lawyer is no longer merely an executor of traditional procedures; they are now required to understand technology, manage its risks, and utilize it in a way that preserves their professional independence, the rights of their clients, and the quality of legal services.